The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/978-981-10-4304-8_4
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Exercise Training on Aerobic Capacity in Patients with Heart Failure and Preserved Ejection Fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is defined as an inability of the ventricles to optimally accept blood from atria with blunted end- diastolic volume response by limiting the stroke volume and cardiac output. The HEpEF prevalence is higher in elderly and women and may be associated to hypertension, diabetes mellitus and atrial fibrillation. Severe exercise intolerance, manifested by dyspnea and fatigue during physical effort is the important chronic symptom in HFpEF patients, in which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…showed that after 3 months of aerobic exercise in preserved heart failure, there were increases in both ventilatory efficiency and aerobic capacity. After aerobic exercise, exertional dyspnea improved during performance in daily living tasks (Prado & Rocco, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…showed that after 3 months of aerobic exercise in preserved heart failure, there were increases in both ventilatory efficiency and aerobic capacity. After aerobic exercise, exertional dyspnea improved during performance in daily living tasks (Prado & Rocco, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that exercise training results in positive cardiovascular outcomes in patients with heart failure 20 . It is known that patient fatigue improves in both patients with cancer and patients with heart failure in response to exercise interventions when these populations are examined individually 14,21 . What is currently unknown is what intervention components are in the exercise interventions in cardio-oncology patients and whether positive cardiovascular and fatigue outcomes from exercise training occur in cardio-oncology patients.…”
Section: Methodsmentioning
confidence: 99%
“…20 It is known that patient fatigue improves in both patients with cancer and patients with heart failure in response to exercise interventions when these populations are examined individually. 14,21 What is currently unknown is what intervention components are in the exercise interventions in cardio-oncology patients and whether positive cardiovascular and fatigue outcomes from exercise training occur in cardio-oncology patients. To answer this, we initially developed the following question that guided our early literature searches: What is known in the existing literature about intervention components of exercise interventions among cardio-oncology patients, and what are the cardiovascular outcomes from these exercise interventions?…”
Section: Identifying Our Research Questionmentioning
confidence: 99%
“…Aerobic exercise training is able to ameliorate dyslipidemia, insulin resistance, endothelial function, and inflammatory status [ 230 ]. It is well known that exercise training exerts beneficial effects in healthy [ 231 ] and in individuals with SAH [ 232 ], T2D [ 233 ], obesity [ 234 , 235 ], cancer [ 236 ], coronary heart disease [ 237 ], and chronic heart failure [ 238 ].…”
Section: Exercise and Cardiovascular Protectionmentioning
confidence: 99%